Rethinking the Paradigm of Economic Development: A Critical Examination of its Intersection with Sustainable Development Goal 4 – Quality Education - Pamella Shabalala Nonkanyiso (Journal of Education, Society & Multiculturalism)
Quality education is an effective instrument for promoting economic development. It equips individuals with the skills and knowledge necessary to secure improved employment, achieve higher earnings and contribute to the economy. This study critically analyses the relationship between economic development and Sustainable Development Goal 4 (SDG 4) – Quality Education within the context of education for sustainable development. It aims to explore the dearth of traditional economic development paradigms in promoting holistic human well-being and propose alternative approaches that prioritise high-quality education to achieve sustainable development. This study draws on the sustainable development concept articulated and expanded by various scholars in the literature that was reviewed. It further explores the principles of education for sustainable development (ESD) as outlined by UNESCO and analyses various economic frameworks such as the Green Economy, Well-being Economics and Doughnut Economics. As a conceptual study, the researcher reviewed existing literature on economic development, sustainable development and education. The study synthesises findings from various studies to critically analyse the interplay between economic growth and quality education. Furthermore, the findings emphasise the potential of ESD in promoting sustainable development. The analysis reveals that traditional economic development paradigms, which focus heavily on GDP growth, often neglect social equity and environmental sustainability, thereby resulting in a failure to advance holistic human well-being. In contrast, integrating quality education as a core component of development strategies may significantly contribute to the progress towards sustainable development. Education empowers individuals, by equipping the with knowledge and skills, encourages critical thinking and promotes environmental stewardship. As a result, education helps to align economic operations with broader social and environmental objectives. This study emphasises the need for policymakers to embrace holistic and inclusive approaches for economic development that give priority to quality education. Reforms in educational systems are necessary to prioritise critical thinking and sustainability. Additionally, investments should be made in teacher training and interdisciplinary learning. The findings support the need to transition from growth-centric development models that prioritise economic growth to models that consider and balance economic, social and environmental objectives, ensuring a future that is both sustainable and equitable.